Performance Measurement in Service and Consultant Company with Balanced Scorecard-AHP - Afifah, Belia; Muflihat, Syakia (Universitas Proklamasi 45, 2024)
PT XYZ is a services and consulting firm that wants to measure the company's overall performance. Currently, the company only measures financial aspects and cannot describe the company's overall performance. It was conducted to measure the company’s performance by identifying key metrics from three perspectives: financial, customer, internal processes, and learning and growth. Underpinned by the Analytical Hierarchy Process weighting system, the Objective Matrix, and the Traffic Light System rating system, the company's performance achieved an overall index score of 9.15. Of a total of 30 KPIs, 10 are yellow KPIs, which means the company's performance is in line with realistic goals, and the remaining 20 are green KPIs. It shows that the company's overall performance is in line with company goals. The 30 KPIs consist of 4 KPIs for financial, 8 KPIs for customer, 12 KPIs for business internal process, and 6 KPIs for learning and growth.